Influence of different loading paths on the multiaxial fatigue behavior of 2024 aluminum alloy under the same amplitude values of the second invariant of the stress deviator tensor (Fracture and Structural Integrity, 2020)
2024 aluminum alloy is a common aeronautic material. During operations, construction elements made of aluminum alloys undertake complex cyclic loadings. Therefore, it is important to estimate the influence of these loadings on the durability of the material. Hereby, multiaxial fatigue tests with the same amplitude values of the second invariant of the stress deviator tensor are conducted, and test data are analyzed. The modified Sines method is utilized to predict fatigue experimental data. Results show that the model is accurate enough to fatigue behavior prediction of 2024 aluminum alloy.
Keywords: Multiaxial fatigue; Tension; Torsion; 2024 aluminum alloy